Why ICANN can't [failings of Internet Corporation for Assigned Names and Numbers]. - Mueller, M. (IEEE spectrum)
In 1998 the US Department of Commerce authorized the Internet Corporation for Assigned Names and Numbers (ICANN) to make them. This nonprofit organization establishes the policies that govern the domain name system. It decides what new top level domains to add to the name system, when to add them, and who will be in charge of them. It settles disputes over name assignments and oversees the dozens of companies, called domain-name registrars, that sell and control domain names. But ICANN is floundering. The organization, based in Marina Del Rey, Calif., has never won over the managers of the country code top-level domains in the rest of the world, such as .uk (United Kingdom) and .de (Germany). Its relations with the root server operators are also strained. The latter maintain the 13 computers around the world in which copies of the key records for the top-level domain names are stored along with their corresponding Internet protocol addresses. Most disturbingly, ICANN recently abandoned its pledge to create a membership structure to elect its powerful, 18-member board of directors. Currently, outside views are in effect excluded because agencies within ICANN, called Supporting Organizations, select most of the board members. At the root of ICANN's troubles is a paralyzing clash of visions of what the organization should be. By regarding itself as a technical priesthood, ICANN has failed as an international policymaking institution